The migration of musical instruments: On the socio-technological conditions of musical evolution. Issue 2 (15th March 2021) - Magnusson, Thor
Abstract : Music technologies reflect the most advanced human technologies in most historical periods. Examples range from 40 thousand years old bone flutes found in caves in the Swabian Jura, through ancient Greek water organs or medieval Arabic musical automata, to today's electronic and digital instruments with deep learning. Music technologies incorporate the musical ideas of a time and place and they disseminate those ideas when adopted by other musical cultures. This article explores how contemporary music technologies are culturally conditioned and applies the concept of ethno-organology to describe the nature of migration of instruments between musical cultures.